Epidemias bioethics in a post-covid world : time for future-facing global health ethics (2020)
The global COVID-19 pandemic posed a multitude of ethics challenges as the realities of the public health emergency became apparent. Issues confronted ranged from the allocation of scarce medical resources to questions about the proper balance of civil liberties and public health–related restrictions to concerns over the harms and benefits of social distancing weighed against those of reopening certain parts of societies. Many faculty in academic bioethics programs across the United States and around the world were asked to help address these and other issues, creating an unprecedented demand for ethics input and analysis. Some issues were familiar to American bioethics scholars. Others were beyond the range of issues and contexts that they typically consider, leading to requests for help from colleagues and participation in collaborative efforts that reflected multidisciplinary perspectives necessary to tackle the problems’ complexities.